Domperidone and maternal milk volume in mothers of premature newborns - Tengku Ellya Fazilla; Guslihan Dasa Tjipta; Muhammad Ali; Pertin Sianturi (Indonesian Pediatric Society, 2017)
Background Mothers of premature newborns often have difficulty giving adequate breast milk volume to their infants. Domperidone is an antagonist of peripheral dopamine receptors and believed to increase breast milk production. In Indonesia, no study has been done to date on the effect of domperidone on maternal milk production in mothers of premature newborns. Objective To evaluate the effect of domperidone on milk production in mothers of premature newborns who failed to lactate.Methods A randomized controlled trial was conducted from July to December 2012 in the Perinatology Unit, Haji Adam Malik Hospital, Medan. Mothers of premature newborns were given lactation counseling for 7 days in order to increase their milk production. Mothers who failed to lactate after that time were enrolled in the study. Fifty subjects were assigned to receive either domperidone or a placebo for 7 days. Milk volume was measured every 2 hours (from 7 am to 9 pm), in the 24 hours before starting therapy, and on the 7th and 10th days (the 10th day being 3 days after stopping therapy). Results This study involved 25 mothers in the domperidone groups and 25 others in placebo group. After 7 days of therapy, mean breast milk volume was significantly higher in the domperidone group than in the placebo group [181.6 (SD 80.2) vs. 72.4 (SD 57.8) mL, respectively; 95%CI of differences 69.36 to 148.93; P=0.0001]. At day 10, breast milk production remained significantly higher in the domperidone group. Furthermore, in the domperidone group, no significant difference in mean breast milk volumes was noted between the 7th and 10th days (P=0.65). Conclusion In mothers of premature newborns who failed to lactate, domperidone therapy for 7 days causes significantly higher milk production compared to placebo.